Transnasal humidified rapid insufflation ventilatory exchange combined with intravenous anesthesia and nerve block without endotracheal intubation for atrial septal defect repair: a case report - Shi, Haifeng; Zhou, Zhengqing; Xu, Hua (Frontiers in Anesthesiology, 2023)
This brief case report describes a new anesthesia method without endotracheal intubation in open heart surgery. The patient was a 41 years old female. Because the location of the atrial septal defect was not suitable for interventional minimally invasive surgery, she could only undergo open heart surgery under cardiopulmonary bypass. Due to news reports about anesthesia without tracheal intubation, the patient refused to undergo tracheal intubation anesthesia; therefore, we innovatively adopted an anesthesia method of transnasal humidified rapid insufflation ventilatory exchange (THRIVE) combined with intravenous anesthesia and nerve block without endotracheal intubation, and achieved success. The whole operation process was very smooth; the patient was quiet and motionless, and her respiration and circulation were stable. After the operation, the patient opened her eyes without any complaints and was safely sent to the CICU (cardiac intensive care unit).